The Long-Term Impact of Parental Divorce on Child Development - Putri Sahara; Izzagita Izzagita (Socrates: Journal of Education, Philosophy and Psychology, 2025)
Parental divorce has a significant impact on children's development, affecting their psychological and social aspects. The main issue raised is how divorce affects children's emotions and behavior, as well as the long-term consequences that may arise due to changes in family dynamics. The aim of this research is to explore the impact of divorce on children, with a focus on changes in behavior and emotional stability. Research goals include identifying factors that influence children's development after divorce and understanding how they adapt to these changes. The method used in this research is a literature review, where the author collects and analyzes various relevant literature sources related to the impact of divorce on children. The search was carried out via Google Scholar with keywords such as and "the impact of parental divorce on children". The focus of analysis includes behavioral changes, emotional stability, and responses to stress. The findings from various articles and previous research are interpreted to provide a comprehensive understanding of the impact of divorce. The research results show that parental divorce has a significant impact on children's psychological development. Many children experience sadness, loneliness, and disappointment after divorce, which can lead to aggressive behavior or withdrawal from social interactions. In addition, the economic instability that often occurs after divorce worsens children's well-being. Although there are some positive impacts such as increased independence, the negative impacts are more dominant and can continue into adulthood. Parental divorce has a significant long-term impact on a child's development, including deep psychological impacts such as low self-esteem and emotional problems. Instability in the family environment and economic difficulties after divorce also hinder children's growth and development. This research emphasizes the importance of support from parents and the community to help children face the challenges caused by divorce, as well as the need for appropriate intervention strategies to support their well-being.